Anisotropic growth of ZnO nanoparticles driven by the structure of amine surfactants: the role of surface dynamics in nanocrystal growth. Issue 21 (16th September 2021) - Wang, Yinping; Coppel, Yannick; Lepetit, Christine; Marty, Jean-Daniel; Mingotaud, Christophe; Kahn, Myrtil L.
Abstract : Amine behavior is strongly related to its structure (tertiary, secondary and primary) and appears to be responsible for the morphology control of nanocrystals. Abstract : Herein, we elucidate the key role of amine surfactants in the controlled anisotropic growth of ZnO nanoparticles that is achieved under mild conditions by organometallic hydrolysis. The structuring influence of alkyl substituents on the nitrogen atom of amines is jointly analyzed theoretically by DFT modeling, and experimentally by multinuclear NMR ( 1 H, 13 C and 17 O) spectroscopy. We demonstrate that in initial steps leading to the growth of colloidal ZnO particles, the nature of molecular species that are involved in the solution strongly depends on the structure of the amine surfactant. By using tertiary, secondary or primary amines, no or weak adducts between the amine and zinc, or stable adducts, or adduct oligomers were identified, respectively. Afterwards, following the course of the reaction, the dynamic behavior of the amines on the grown ZnO nanocrystal surfaces is also strongly correlated with their structure. We identified that in the presence of tertiary, secondary or primary amines, no significant [Zn⋯N] adsorption, or surface adsorption with notable surface mobility, or a very strong adsorption is achieved, respectively. The last case, primary amines, significantly involves the structuring of a hydrogen bonding network. Therefore, such surface dynamic behavior has a predominant role in driving the nanocrystal growth, and orienting the ZnO material final morphology. By forming hydrogen bonds at the nanoparticle surface during the growth process, primary amines specifically lead to the formation of nanorods. Conversely, isotropic nanoparticles and aggregates are obtained when secondary and tertiary amines are used, respectively. These findings shed light on the role of weak surface interactions, herein H-bonding, that rule the growth of nano-objects and are as such crucial to identify, study, and control for achieving progress in nanoscience.